2021
DOI: 10.5093/psed2021a29
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotional Intelligence in Adolescent Bullying: A Systematic Review

Abstract: Adolescence is a transition period between childhood and adulthood, marked by the development of autonomy, personality, and identity. In this period, relationships with peers play an important role. Therefore, experts advise focusing on adolescence to reduce possible long-term risks (Gómez-Ortiz et al., 2020; Sánchez-Ventura & Grupo PrevInfad/PAPPS Infancia y Adolescencia, 2012). Many of these peer interactions take place within the school environment, where children and adolescents spend a large part of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
4
0
7
Order By: Relevance
“…From this point of view, it is advisable to generate training plans for management teams, professionals, and parents, creating spaces for collaboration, reflection, and analysis that improve coexistence, while addressing the impact of bullying to provide an effective and early response to this phenomenon . The results of a recent systematic review revealed the importance of designing and implementing programs of EI in the school context as prevention and action against bullying (Rueda et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, it is advisable to generate training plans for management teams, professionals, and parents, creating spaces for collaboration, reflection, and analysis that improve coexistence, while addressing the impact of bullying to provide an effective and early response to this phenomenon . The results of a recent systematic review revealed the importance of designing and implementing programs of EI in the school context as prevention and action against bullying (Rueda et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…investigación ha demostrado consistentemente los beneficios que supone tener IE tanto en adolescentes como en adultos. En concreto, mayores niveles de IE se han asociado con una mejor salud mental y bienestar (Davis y Humphrey, 2012; Domínguez-García y Llamas-Díaz et al, 2023), y un mejor ajuste en diferentes contextos tanto académicos como personales (García-Sancho et al, 2014;Gutiérrez-Cobo et al, 2023;MacCann et al, 2020;Rueda et al, 2022;Vega et al, 2022). En el ámbito profesional, numerosos estudios empíricos centrados en las organizaciones han demostrado sistemáticamente que la IE desempeña un papel decisivo en aspectos cruciales como la satisfacción laboral, el burnout, el compromiso y el rendimiento laboral (Joseph et al, 2015;Joseph y Newman, 2010;Miao et al, 2017;O'Boyle et al, 2011;Wang et al, 2022).…”
Section: Launclassified
“…Hal ini diperkuat dengan pendapat Thomas (dalam Umaroh, 2017) yang menyatakan bahwa dalam lingkungan sekolah yang negatif dapat meningkatkan permasalahan perilaku pada siswa. Bullying merupakan hal yang umum terjadi di sekolah sehingga dianggap wajar karena sebagian besar waktu siswa berada di sekolah (Rueda et al, 2022). Tindak agresi ini ditunjukkan dalam bentuk tindakan bullying terhadap teman sebayanya disekolah.…”
Section: Pendahuluanunclassified